DISTRIBUTION OF HETEROCYSTOUS CYANOBACTERIA IN RICE FIELDS OF CUDDALORE DISTRICT, TAMILNADU: Life Science-Botany - K. THAMIZH SELVI; K. SIVAKUMAR (International Journal of Life Science and Pharma Research, 2012)
Cyanobacteria forms a large group of structurally complex and ecologically significant gram negative prokaryotes which flourish in rice fields and also known to sustain the fertility of this ecosystem. This study is aimed to characterize the abundance of cyanobacteria in rice field areas in Cuddalore District, Tamilnadu. A total of 30 heterocystous forms from 7 genera comes under a single order with 3 families were recorded. The present study concludes that the density of heterocystous forms which enhances soil fertility